2013
DOI: 10.1039/c2cp42722b
|View full text |Cite
|
Sign up to set email alerts
|

A comparative VCD study of methyl mandelate in methanol, dimethyl sulfoxide, and chloroform: explicit and implicit solvation models

Abstract: Vibrational absorption (VA) and vibrational circular dichroism (VCD) spectra of methyl mandelate, a prototype chiral molecule, in a series of organic solvents, namely methanol (MeOH-d(4)), dimethyl sulfoxide (DMSO-d(6)), and chloroform (CDCl(3)), have been measured in the finger print region from 1800 to 1150 cm(-1). Implicit solvation models in the form of polarizable continuum model and explicit solvation models have been employed independently and simultaneously. The goal is to evaluate their efficiencies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…Several approaches have been used by researchers. One elaborative approach is to utilize classical MD or Car‐Parrinello MD (CPMD) to create a chiral solute in equilibrium with a box of water molecules ,. Very recently, the first fully ab initio MD calculation of dynamical VCD spectrum of propylene oxide in the liquid phase was reported, which reproduced much of the experimental data although the theoretical prediction of the induced solvent VCD signal was still buried in simulation noise .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several approaches have been used by researchers. One elaborative approach is to utilize classical MD or Car‐Parrinello MD (CPMD) to create a chiral solute in equilibrium with a box of water molecules ,. Very recently, the first fully ab initio MD calculation of dynamical VCD spectrum of propylene oxide in the liquid phase was reported, which reproduced much of the experimental data although the theoretical prediction of the induced solvent VCD signal was still buried in simulation noise .…”
Section: Resultsmentioning
confidence: 99%
“…These studies pointed out the importance of both explicit and implicit solute‐solvent interactions in modelling solvent effects, for example for solvents which can serve as a hydrogen (H)‐bond donor/acceptor to a solute. For many common solvents, such as chloroform and dimethyl sulfoxide (DMSO), one can adequately account for solvent effects by constructing small solute‐solvent H‐bonded complexes and placing them in a bulk solvent which is commonly modelled by the polarizable continuum model (PCM) ,,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…c Percent abundance at 323 K, the source temperature, based on relative free energy. 21 While no corresponding study has been reported for MBF, for the sake of discussion, we tentatively assume that the aforementioned dihedral angles remain approximately the same for both MBF and MM in methanol solution as in the gas phase. five-membered ring is no longer nearly planar.…”
Section: Computationalmentioning
confidence: 88%
“…17 Le Barbu-Debus et al assigned their double-resonance IR/UV spectrum of MM in the gas phase to the latter conformer, containing an OHÁ Á ÁOQC intramolecular hydrogen bond, which they also calculated to be the minimum energy conformer. 21 Finally, Shi et al used MM as a representative species in their computational model of chirality recognition. 19 Furthermore, Nedić and Suhm characterized crystalline MM using Fourier-transform infrared microspectroscopy, 20 and Poopari et al characterized solvated MM using vibrational circular dichroism.…”
Section: Introductionmentioning
confidence: 99%